Influence of dental erosion on shear bond strength of ceramic brackets bonded with two different adhesive systems: an in vitro study - Laerte Ribeiro Menezes-Júnior; Marcos Alan Vieira Bittencourt; Andomar Bruno Fernandes Vilela; Carlos José Soares; Diego Figueiredo Nóbrega; Renata Marques de Melo Marinho; Sigmar de Mello Rode; Flávia Pardo Salata Nahsan; Luiz Renato Paranhos (Bioscience Journal, 2021)
This study aimed to analyze the shear bond strength (SBS) of ceramic orthodontic brackets bonded with two different adhesive systems to intact and eroded teeth. Ceramic brackets were bonded to 72 bovine central incisors divided into four groups, defined by two study factors: enamel condition (control group, kept in artificial saliva; and experimental group, eroded by using immersion cycles in Coke™ for 90 seconds, every six hours for five days), and adhesive system type (Transbond™ XT or Transbond™ Plus Color Change). Polycrystalline ceramic brackets were adhesively fixed on all specimens using the same light curing protocol. SBS was tested using 0.5 mm/min and the failure mode was classified. SBS data was analyzed using two-way ANOVA followed by Tukey test. The adhesive remnant index (ARI) scores were analyzed using Kruskal-Wallis test with Dunn's post-hoc pairwise comparison (α=0.05). Percentages of ARI scores between the groups were compared by Fisher’s exact test. Spearman's correlation coefficient was applied to investigate the correlation between ARI scores and SBS values. Only the adhesive system factor had significant effect on SBS (p=0.014), Transbond™ Plus Color Change showing higher values. No significance was found for enamel condition (p=0.665) or the interaction between adhesive system and enamel condition (p=0.055). ARI scores frequencies differed between groups (p<0.001). The median ARI scores were statistically different for most comparisons among the groups. However, no significant correlation was found between ARI scores and SBS. In conclusion, the type of adhesive system affected the SBS of ceramic brackets to dental enamel, but the enamel condition, intact or eroded, had no significant effect. There was no correlation between ARI scores and SBS values, although eroded enamel tended to retain more adhesive after bracket removal.